Rheological variations and industrial quality of bread wheat in Sonora - Rodríguez-Pérez, Gilberto; Quintana-Camargo, Martín; Latournerie-Moreno, Luis; Gámez-Vázquez, Alfredo Josué; Ávila-Perches, Miguel Ángel; Verduzco-Miramón, Francisco Javier (Revista Mexicana de Ciencias Agrícolas, 2025)
Wheat represents about 12% of the total value of agricultural imports in Mexico; it is mostly used to make bread, pasta, cookies, and flour tortillas. The research aimed to determine the rheological variation in dough and industrial quality of 12 advanced lines of bread wheat. The experiment was established in the Yaqui Valley under a randomized complete block design with three replications at an average temperature of 17.1 °C. The unit consisted of four rows 3 m long and 80 cm apart in double rows, on two sowing dates of the 2020-2021 agricultural cycle. The variables assessed were hectoliter weight and weight of one thousand grains, protein in flour, strength, tenacity/extensibility, grain hardness, and bread volume. The results show statistical differences between the main factors (dates, lines) and their interaction in all variables; the functional properties in flour and values in selection indices favored L-5, L-2, L-3, L-7, and Borlaug; a positive correlation was found between physical and chemical traits. In conclusion, sowing in November favored the concentration of protein in the grain and associated with strong and extensible dough, it showed higher volumes of bread.
Keywords: Triticum aestivum; industrial quality; rheological properties